The fight against health threats from wildlife in Dong Nai, Vietnam - International Livestock Research Institute (International Livestock Research Institute, 2024)
From 2003 to 2015, Dong Nai Province, Vietnam battled avian influenza and rabies, leading to the creation of Coordination Regulation 6552 in 2022. This regulation operationalizes the One Health approach at the ground level, strengthening collaboration between the health and agriculture sectors for effective response to zoonotic diseases. Supported by the CGIAR One Health Initiative, the One Health approach integrates human, animal and environment health, with community interventions ensuring disease control.